Probing the top-Higgs sector with composite Higgs models at present and future hadron colliders - Bautista, Carlos [UNESP]; de Lima, Leonardo; D’Elia Matheus, Ricardo [UNESP]; Pontón, Eduardo [UNESP]; Fernandes do Prado, Leônidas A. [UNESP]; Savoy-Navarro, Aurore (Springer Nature, 2021)
We study the production of tt¯ h and tt¯ hh at hadron colliders, in the minimal Composite Higgs Models, based on the coset SO(5)/SO(4). We explore the fermionic representations 5 and 14. A detailed phenomenological analysis is performed, covering the energy range of the LHC and its High Luminosity upgrade, as well as that of a future 100 TeV hadron collider. Both resonant and non-resonant production are considered, stressing the interplay and complementary interest of these channels with each other and double Higgs production. We provide sets of representative points with detailed experimental outcomes in terms of modification of the cross sections as well as resonance masses and branching ratios. For non-resonant production, we gauge the relative importance of Yukawa, Higgs trilinear, and contact tt¯ hh vertices to these processes, and consider the prospect for distinguishing the fermion representations from each other and from the Standard Model. In the production of top partners, we find that the three-body decay channel W+W–t becomes significant in certain regions of parameter space having a degenerate spectrum, and is further enhanced by increasing the top partner’s mass. This motivates both higher energy machines as well as the need to go beyond the current analysis performed for the searches for these resonances.
Keywords: Beyond Standard Model; Higgs Physics; Technicolor and Composite Models